Influence of structurally related micelle forming surfactants on the antioxidant activity of natural substances. (December 2019) - Battista, Sara; Campitelli, Patrizio; Carlone, Armando; Giansanti, Luisa
Graphical abstract: Highlights: The aggregation properties of cationic or zwitterionic ( N -oxide moiety) structurally related surfactants were investigated. The antioxidant activity of hydrophobic (+)-usnic acid and hydrophilic L -ascorbic acid in presence of micelles was studied. Antioxidant effectiveness depends on surfactant chain length, charge, pH and hydrophilicity and localization of the solute. Abstract: Physicochemical properties of micelles, like other lipid aggregates, mostly depend on the composition and on the structure of the surfactants used as monomers. The preparation and the characterization of three cationic L -prolinol derivative surfactants with different chain lengths and their corresponding N -oxide are described. UV measurements were carried out to investigate the effect of the inclusion in micelles on the degradation of L -ascorbic acid and (+)-usnic acid. An influence on antioxidant activity was exerted to an extent strictly dependent on i ) surfactant chain length, ii ) charge, iii ) pH (in the case of (+)-usnic acid) and iv ) on the hydrophilicity of the solute, determinant parameter for their location in the aggregates. In general the extent of the antioxidant activity of the system in the case of N -oxides micelles depends on surfactant chain length. On the other hand, cationic micelles formed by the surfactant with the shortest chain behave more like N -oxides ones rather than those formed by its relative structural homologues featuring longer alkyl chains, probably as a consequence of a concentration effect.